PENGARUH PERIODE PANEN TERHADAP VIABILITAS BENIH ROSELA (Hibiscus sabdariffa L.) - Dedes Mayang Sari Pulungan; Haryati Haryati; Ratna Rosanty Lahay (Universitas Sumatera Utara, 2014)
Roselle has a harvest period that does not simultaneously or concurrently so that harvesting donegradually. To obtain a good quality seed of roselle harvesting seeds based physiologically mature.This research aimed to determine effect of harvest periode for seeds viability of roselle (Hibiscussabdariffa L.). This research has conducted in the experimental field which were ± 25 meters abovesea level and continued in Seed Technology Laboratory of the Faculty of Agriculture, UniversitasSumatera Utara from February to June 2013, using the non factorial completely randomized design.Analyzed of the data using analysis of variance and continued with DMRT. The result of researchhas identified that it has significantly effect of harvest period that influenced weight of 100 seeds(g), number of seeds/fruit (seed), normal germination (%), seeds do not germinate (%), seedling dryweight (g), but it was not significantly to rate of germination (days), abnormal germination (%) andvigor index (%).Keywords: harvest period, viability, seed of roselle